TO THE SOLUTION OF SOME PROBLEMS OF DEVELOPING ASSEMBLY TECHNOLOGY BY MODELING ASSEMBLIES IN CAD SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Considers the features of the automated design of technological processes of assembly of products in mechanical engineering, in terms of their impact on production processes.